1997
DOI: 10.3390/21200186
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of α,β-Unsaturated Ketones Bearing a Trifluoromethyl Group and Their Application in Organic Synthesis

Abstract: Abstract:The approaches to the synthesis of α,β-unsaturated CF 3 -containing ketones and their use in organic chemistry are reviewed. The synthetic applications of these ketones are discussed. The formation of 4-, 5-, 6-and 7-membered heterocycles bearing a CF 3 group based on reactions of α,β-unsaturated CF 3 -containing ketones with different nucleophiles are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
45
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(46 citation statements)
references
References 91 publications
1
45
0
Order By: Relevance
“…3). Similar nucleophilicity of the two nucleophilic centers of Hydrazine was cited by Nenajdenko 15 , et al as the reason behind the possibility of attack of the nucleophile at both the double bond and the carbonyl group. Due to methyl group substitution of MMH, two regioisomers of pyrazoline were expected to be formed UV-Vis study of this interaction in acetonitrile medium (Fig.…”
Section: Chemical Structure and Reaction Mechanismmentioning
confidence: 75%
See 2 more Smart Citations
“…3). Similar nucleophilicity of the two nucleophilic centers of Hydrazine was cited by Nenajdenko 15 , et al as the reason behind the possibility of attack of the nucleophile at both the double bond and the carbonyl group. Due to methyl group substitution of MMH, two regioisomers of pyrazoline were expected to be formed UV-Vis study of this interaction in acetonitrile medium (Fig.…”
Section: Chemical Structure and Reaction Mechanismmentioning
confidence: 75%
“…4) showed that there is a decrease in absorbance for the peak at 320 nm which is followed by the formation of new peak at lower wavelength (232 nm). Decrease in absorbance for the peak at 320 nm is indicative of involvement of double bond and carbonyl group in the reaction leading to disturbance of the conjugation in the side chain of thiophene moiety and hence pyrazoline formation 11,15 . Due to hydrazine interaction, wave length at 229 nm is shifted to higher wavelength (232 nm).…”
Section: Chemical Structure and Reaction Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the 1970s, according to previous publications, [20][21][22][23] research groups have reported the systematic synthesis of 4-substituted 4-alkoxy-1,1,1-trihaloalk-3-en-2-ones (1) from the trihaloacetylation reaction of the respective enolethers (1a, 1b) or acetals (1c-i) with trifluoracetic anhydride or trichloroacetyl chloride, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, 4-alkoxy-4-(alkyl/aryl/heteroaryl)-1,1,1-trifluoro(chloro)alk-3-en-2-ones are versatile precursors for the heterocyclic synthesis and direct construction of this type of heterocycles. [20][21][22][23] In this context and in an attempt to develop synthetic methods to obtain acyl spacer heterocycles and new fluorinated molecules, herein we report a practical and regioselective methodology for the preparation of a series of 1,4-bis …”
Section: Introductionmentioning
confidence: 99%